Quality Education and Impact on Sustainable Development Goals - Kharbanda, Siddharth (JOURNAL OF INDIAN EDUCATION, 2024)
Education is a narration of lifelong learning and entails history of international priority. Education is not an end in itself but a means to an end. It serves as a medium of implementing SDGs through literacy, awareness, and a unified process of broadcasting information for its propagation and expansion. To ensure fulfillment of this right, we must provide universal access to inclusive, and equitable quality education and learning, thus, ‘leaving no one behind’. Education aims at the development of the human personality, and promotes mutual understanding, tolerance, friendship and peace. It is applied knowledge to understand contexts and gain insights. Considering the need of the hour and the importance of education in sustainable development, this paper delves into the factors affecting quality education with a statistical outcome of the study. As per the United Nations, quality education lays the framework to ensure inclusive, equitable, and quality education and promote lifelong learning opportunities for all. Quality education greatly impacts the efficacy of learning potential for empowering human capital. SDG 4 supports the reduction of disparities and inequities in education, both in terms of access and quality. It recognises the need to provide quality education for all, especially vulnerable population, including the poor, children living in rural areas, persons with disabilities, indigenous community and refugees. The objective of this study is to understand the critical importance of quality education and its transformative effects on other SDGs.